2019
DOI: 10.1111/ijcp.13419
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin 1‐1 phenotype: A risk factor for 24‐hours polyuria

Abstract: Background Haptoglobin (Hp) displays three major phenotypes (Hp 1‐1, Hp 2‐2 and Hp 2‐1). Hp 1‐1 has been implicated in high blood pressure and salt sensitivity, and thus may mediate excess urine production. Aim To explore the relationship between Hp polymorphisms and polyuria (>40 mL/kg/24 hours). Methodology Post hoc analysis of a prospective observational study of subjects who completed a renal function profile between October 2011 and February 2015 (n = 170). Hp phenotypes were determined by starch gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In our previously published study, we demonstrated that Hp polymorphism-related salt sensitivity in Hp1-1 phenotype lacked circadian rhythm in diuresis, renal clearance of free water, and sodium, in contrast to Hp2-2/2-1 phenotypes [ 18 ]. Hp is a haemoglobin clearing plasma protein that displays three major phenotypes in humans as Hp 1-1, Hp 2-2, and Hp 2–1 [ 33 ], and Hp1‐1 has been associated in high BP and salt sensitivity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previously published study, we demonstrated that Hp polymorphism-related salt sensitivity in Hp1-1 phenotype lacked circadian rhythm in diuresis, renal clearance of free water, and sodium, in contrast to Hp2-2/2-1 phenotypes [ 18 ]. Hp is a haemoglobin clearing plasma protein that displays three major phenotypes in humans as Hp 1-1, Hp 2-2, and Hp 2–1 [ 33 ], and Hp1‐1 has been associated in high BP and salt sensitivity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previously published study, haptoglobin (Hp) polymorphism-related salt sensitivity in sodium and water handling were reported [ 18 ]. In this study, we hypothesized that healthy individuals who display a low rate of sodium excretion after an acute high salt load react inappropriately with salt and water retention and are therefore called “salt-sensitive”.…”
Section: Introductionmentioning
confidence: 99%